Correlation Between Learning Motivation and Students’ Responses on the Implementation of the ADERiC Learning Model - Muhammad Syahrul Kahar; Abdul Haris Panai; Mursalin Mursalin; Zulaecha Ngiu; Novianty Djafri; Asna Aneta (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The learning model is determined and selected by teachers to stimulate students’ learning motivation and responses, which play an important role in the learning process. The purposes of the study are to identify a correlation between students’ learning motivation and their responses o non the implementation of the ADERiC model. The study was conducted at the University of Muhammadiyah Sorong, involving ten students. Data were analyzed using Pearson correlation and covariance techniques. The research findings show that based on the questionnaire students’ responses, each item of the implementation of the ADERiC learning model was in the high classification, and the highest was the observation of persistence in learning. Besides that, there is a correlation between students' learning motivation and responses to implementing the ADERiC model. Therefore, implementing the learning model should stimulate and push students’ understanding.